2021
DOI: 10.1111/hsc.13279
|View full text |Cite
|
Sign up to set email alerts
|

Motherhood and assisted reproduction in a religious context: Genes, stigma and supports in Utah, United States

Abstract: Six percent of cisgender (i.e. not transgender) women aged 15-44 are considered infertile in the United States, and 12% are unable to carry a pregnancy to term. For those who yearn to create a family despite these circumstances, assisted reproductive technology (ART) is an often-utilised resource. Though faith-based institutions have been referenced as a source of support for involuntarily childless adults, it is unclear how religious doctrine, especially that which prizes 'traditional' gender roles and geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…African American women with infertility also described that the cultural ideologies placed on them from their community led them to feel stigmatized (Ceballo et al, 2015). Christian American women shared commonalities with women in the present review as they also discussed experiencing stigma due to the inability to fulfill their cultural role of bearing children (Gezinski et al, 2021). Women with infertility from the United States discussed being socially excluded or alienated from specific social or religious ceremonies and feeling stigmatized from their community because of the quiet nature of infertility (Gezinski et al, 2021).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…African American women with infertility also described that the cultural ideologies placed on them from their community led them to feel stigmatized (Ceballo et al, 2015). Christian American women shared commonalities with women in the present review as they also discussed experiencing stigma due to the inability to fulfill their cultural role of bearing children (Gezinski et al, 2021). Women with infertility from the United States discussed being socially excluded or alienated from specific social or religious ceremonies and feeling stigmatized from their community because of the quiet nature of infertility (Gezinski et al, 2021).…”
Section: Discussionmentioning
confidence: 83%
“…Low self-esteem or a negative self-concept make it extremely difficult for some women who experience infertility to cope. Similar to American women, who discussed feeling sad, bitter, angry, or upset with themselves for the inability to become pregnant (Gezinski et al, 2021), women from Turkey, Pakistan, Jordan, and Gambia shared that their experiences with infertility often resulted in feelings of anxiety, stress, and depression ( Batool & de Visser, 2016;Dierickx et al, 2018;Höbek Akarsu & Kızılkaya Beji, 2021;Karaca & Unsal, 2015;Mete et al, 2020;Obeidat et al, 2014). and Mumtaz et al (2013) reported that women with infertility are highly stigmatized in Iran due to societal pressure to have children; as a result, they endure psychological abuse from those around them.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Specifically, religiosity and conservative right-wing ideology are related to lower acceptance of ARTs (Herrera et al, 2015;Irrázabal and Johnson, 2019). In this collective, they generate feelings of guilt, anguish, social isolation, rejection of ARTs, and social stigmatization of ART users, concluding that throughout the ART process, religion, and spirituality should be included as support for people who identify as such (Gezinski et al, 2021).…”
Section: Attitudes Variables and Assisted Reproductionmentioning
confidence: 99%